The Effect of Kelulut Honey (Trigona spp.) Concentration as a Natural Sugar on the Quality of Mung Bean Soyghurt (Vigna radiata L.) - Eka Yuniar Retno Lamdari; Rudiana Agustini (Jurnal Pijar MIPA (Pengkajian Ilmu dan Pengajaran Matematika dan Ilmu Pengetahuan Alam), 2025)
Mung bean soyghurt is a fermented functional food product developed from plant-based milk derived from mung beans (Vigna radiata L.). Lactic acid bacteria (LAB) are employed as the fermentative agents in the fermentation process, with the addition of kelulut honey (Trigona spp.) serving as a natural nutrient source. This product contains both probiotic microorganisms and prebiotic components, offering potential health-promoting properties. This research aimed to was conducted to assess the impact of varying concentrations of kelulut honey, used as a natural sugar, on the quality of mung bean soyghurt. Fermentation was carried out at 37 °C  for 8 hours with kelulut honey incorporated at concentrations of 0%, 5%, 10%, and 15% (v/v), along with 0,5 gram of probiotic starter. The resulting products were analyzed for LAB growth, total titratable acidity (TTA), and pH. LAB populations were determined using the Total Plate Count (TPC) method, titratable acidity was determined through acid-base titration, and pH was assessed using a calibrated pH meter. The results showed that increasing concentrations of kelulut honey significantly enhanced LAB growth and TTA while reducing pH values. The honey also influenced organoleptic properties, including color, aroma, and taste. The best treatment was observed in the formulation containing 10% kelulut honey, which yielded a LAB count of 4,20 × 108 CFU/mL, a TTA of 1,638%, a pH of 4,00, and organoleptic characteristics that received favourable evaluations from the panellists across all assessed parameters.